2023
DOI: 10.4081/ejh.2023.3526
|View full text |Cite
|
Sign up to set email alerts
|

LINC00926 is involved in hypoxia-induced vascular endothelial cell dysfunction <em>via</em> miR-3194-5p regulating JAK1/STAT3 signaling pathway

Abstract: Vascular endothelial cell (VEC) dysfunction is associated with the development of coronary heart disease (CHD). Long intergenic non-protein coding RNA 926 (LINC00926), a kind of long noncoding RNA (lncRNA), has been found to be abnormally expressed in CHD patients. However, the biological role of LINC00926 has not been reported. In our research, we intended to explore the regulatory mechanism of LINC00926 in hypoxia-exposed HUVEC cells (HUVECs). In our in vitro study, HUVECs were exposed under hypoxic conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In addition, they can also serve as miRNA sponges to disturb target mRNA mediated by miRNA to resolve. Thereinto, Bam et al found in their research on post-traumatic stress disorder that LINC00926 controls the expression of IFNG and IL17A through physical interactions with MLL1, suggesting that LINC00926 regulates the expression of WNT10B and thereby regulates in ammation [26].Jiang et al found that linc00926 regulates the JAK1/STAT3 signaling pathway through miR-3194-5p, inhibits cell proliferation, migration, and tube formation, and increases cell apoptosis, thereby participating in hypoxia induced vascular endothelial cell dysfunction [27].Linc00861 was found to be a potential intervention target for immunotherapy in prostate cancer patients, which is signi cantly correlated with PD-1 and CTLA4 [28]. In the study of uterine cancer, it was found that the LINC00861/miR-513b-5p axis may inhibit the EMT process of cancer cells through the PTEN/AKT/mTOR signaling pathway [29].The overexpression of linc00294 signi cantly alleviates LPS induced survival inhibition and in ammatory damage in human umbilical vein endothelial cells (HUVECs) [30].In addition, our study found that mir5195 is co-expressed with 17 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they can also serve as miRNA sponges to disturb target mRNA mediated by miRNA to resolve. Thereinto, Bam et al found in their research on post-traumatic stress disorder that LINC00926 controls the expression of IFNG and IL17A through physical interactions with MLL1, suggesting that LINC00926 regulates the expression of WNT10B and thereby regulates in ammation [26].Jiang et al found that linc00926 regulates the JAK1/STAT3 signaling pathway through miR-3194-5p, inhibits cell proliferation, migration, and tube formation, and increases cell apoptosis, thereby participating in hypoxia induced vascular endothelial cell dysfunction [27].Linc00861 was found to be a potential intervention target for immunotherapy in prostate cancer patients, which is signi cantly correlated with PD-1 and CTLA4 [28]. In the study of uterine cancer, it was found that the LINC00861/miR-513b-5p axis may inhibit the EMT process of cancer cells through the PTEN/AKT/mTOR signaling pathway [29].The overexpression of linc00294 signi cantly alleviates LPS induced survival inhibition and in ammatory damage in human umbilical vein endothelial cells (HUVECs) [30].In addition, our study found that mir5195 is co-expressed with 17 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR‐590‐5p expression was markedly reduced in CRC, and its overexpression suppressed the malignant behaviors of cancer cells 10 . A previous study showed that miR‐3194‐5p knockdown suppressed the proliferation, migration, and tube formation of hypoxia‐treated vascular endothelial cells and increased cell apoptosis 11 . Young et al demonstrated that the estradiol‐mediated inhibition of SP1 decreased miR‐3194‐5p expression, promoting lung cancer progression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study showed that miR-3194-5p knockdown suppressed the proliferation, migration, and tube formation of hypoxia-treated vascular endothelial cells and increased cell apoptosis. 11 Young et al demonstrated that the estradiolmediated inhibition of SP1 decreased miR-3194-5p expression, promoting lung cancer progression. 12 In addition, Hufbauer et al revealed that miR-3194-5p was highly expressed in primary human papillomavirus type 16 oropharyngeal squamous-cell-carcinoma and matched metastasis.…”
mentioning
confidence: 99%